2011
DOI: 10.1203/pdr.0b013e3182321128
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Neuromotor Outcome in School-Age Children With Congenital Hypothyroidism Receiving Early High-Dose Substitution Treatment

Abstract: Congenital hypothyroidism (CH) can lead to intellectual deficits despite early high-dose treatment. Our study aimed to determine whether motor impairments can occur despite early highdose treatment. Sixty-three children with CH and early (median age of onset of treatment 9 d), high-dose treatment (median starting dose of levothyroxine 14.7 g/kg/d) were tested with the Zurich Neuromotor Assessment (ZNA) at a median age of 13.8 y (range 7.0 -14.2 y). Median z-scores in the children with CH were Ϫ0.95 in the pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
17
0
4
Order By: Relevance
“…Subtle and specific memory deficits and reduced hippocampal volumes may be observed ( 117 ). There is also a risk of fine motor impairment ( 118 ). However, most early-treated patients are well integrated into society with no impairment in educational level ( 46 ).…”
Section: 0 Outcomes Of Treated Patientsmentioning
confidence: 99%
“…Subtle and specific memory deficits and reduced hippocampal volumes may be observed ( 117 ). There is also a risk of fine motor impairment ( 118 ). However, most early-treated patients are well integrated into society with no impairment in educational level ( 46 ).…”
Section: 0 Outcomes Of Treated Patientsmentioning
confidence: 99%
“…In children with congenital hypothyroidism examined between 7 and 14 years of age, a significantly poorer performance was found in gross and fine motor functions, and the researchers concluded that problems with fine motor skills may be associated with visuomotor and visuospatial changes, besides problems with memory and attention (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Given that the major alterations in children with CH are focused on several areas, but particularly in motor (7) and language skills (11)(12)(13) , the objectives of this study were to screen the global development of children with and without congenital hypothyroidism and to investigate the relationship between fine motor skills and expressive language skills in these two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this other studies have shown behavior problems like increased anxiety, social withdrawal and poor concentration with higher doses in children at age of 8 years. Thus demonstrating potential dangers of overtreatment with levothyroxine in CH children [52].…”
Section: Target Concentrationsmentioning
confidence: 97%